2022
DOI: 10.3390/polym14235130
|View full text |Cite
|
Sign up to set email alerts
|

p-Type PVA/MWCNT-Sb2Te3 Composites for Application in Different Types of Flexible Thermoelectric Generators in Combination with n-Type PVA/MWCNT-Bi2Se3 Composites

Abstract: This work is devoted to the fabrication of p-type polyvinyl alcohol (PVA)-based flexible thermoelectric composites using multiwall carbon nanotubes-antimony telluride (MWCNT-Sb2Te3) hybrid filler, the study of the thermoelectrical and mechanical properties of these composites, and the application of these composites in two types (planar and radial) of thermoelectric generators (TEG) in combination with the previously reported PVA/MWCNT-Bi2Se3 flexible thermoelectric composites. While the power factors of PVA/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…In addition, low-intensity diffraction peaks related to Sb 2 O 3 ( Figure 1 d, blue curve) and Te ( Figure 1 d, green curve) were observed, indicating the presence of native oxide layer on the Sb 2 Te 3 nanostructures, as well as possible inclusion of clusters of Te in the Sb 2 Te 3 -MWCNT heterostructures. These results are consistent with the previously reported for the MWCNT-Sb 2 Te 3 heterostructures [ 13 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, low-intensity diffraction peaks related to Sb 2 O 3 ( Figure 1 d, blue curve) and Te ( Figure 1 d, green curve) were observed, indicating the presence of native oxide layer on the Sb 2 Te 3 nanostructures, as well as possible inclusion of clusters of Te in the Sb 2 Te 3 -MWCNT heterostructures. These results are consistent with the previously reported for the MWCNT-Sb 2 Te 3 heterostructures [ 13 ].…”
Section: Resultssupporting
confidence: 94%
“…For the fabrication of flexible films containing encapsulated Sb 2 Te 3 -MWCNT or bare MWCNTs, the heterostructures were deposited on polyimide substrates, then coated with PDMS (Sigma-Aldrich, Inc., St. Louis, MI, USA), cured for 10 min in 150 °C, and then the resulting elastic film was lifted off the glass using tweezers. For the fabrication of mixed composite, the Sb 2 Te 3 -MWCNT heterostructures were deposited on glass substrates, then scrapped off the substrates and mixed in PVA (Sigma-Aldrich, Inc., St. Louis, MI, USA) as described elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been shown that direct deposition of bismuth or antimony chalcogenides on pre-fabricated CNT scaffolds results in a formation of flexible n-type CNT-Bi2Se3 or p-type CNT-Sb2Te3 hybrid networks, exhibiting Seebeck coefficients comparable with the values reported for bulk Bi2Se3 or Sb2Te3 [3]. Recently, an approach of the application of CNT-Bi2Se3 and CNT-Sb2Te3 hybrid networks for the fabrication of n-type and p-type PVA-based TE composites and the development of flexible TEG has been demonstrated [4]. However, the thermoelectric efficiency of these composites was low due to the high resistance of the nanocomposites.…”
Section: Extended Abstractmentioning
confidence: 89%